(3GdLGeY GdUMjMs - (3eMeO Hf ESeGYjd Hf EHQGgje GdLYaj GdHNGQj, CHh YHO Gddg , J (B256 (3g` s ((3HYdHc s)
(3ChdgG (B:s
(3cJGH GdCTQHI hbhd Gddg JYGdi (B(((3hEfeG GdNeQ hGdejSQ (B))q s
(3BNQgG (B:s
(3Je cJGH GdLGeY GdUMjM hddg GdMeO hGdefI s
(3GdfSNI HgG MhGTs
(3GdfSNI ebGHdI ceG ai BNQgGs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs